2009
DOI: 10.1161/circoutcomes.108.829523
|View full text |Cite
|
Sign up to set email alerts
|

Economic Impact of Angina After an Acute Coronary Syndrome

Abstract: Background-Angina in patients with coronary artery disease is associated with worse quality of life; however, the relationship between angina frequency and resource utilization is unknown. Methods and Results-Using data from the MERLIN-TIMI 36 trial, we assessed the association between the extent of angina after an acute coronary syndrome (ACS) and subsequent cardiovascular resource utilization among 5460 stable outpatients who completed the Seattle Angina Questionnaire at 4 months after an ACS and who were th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
88
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(89 citation statements)
references
References 35 publications
1
88
0
Order By: Relevance
“…Validated standardized instruments were used to assess psychosocial and health status. These included (1) depression using the 9‐item Patient Health Questionnaire (PHQ‐9), with higher scores indicating increasing severity (range 0–27)19, 20, 21, 22; (2) perceived stress using the 14‐item Perceived Stress Scale (PSS), with higher scores indicating higher stress levels (range 0–40)23, 24; and (3) health status outcomes (patients’ physical limitations, angina frequency, and quality of life related to angina) using the Seattle Angina Questionnaire (SAQ; scores ranging from 0 to 100), with higher scores indicating better health status 25, 26, 27, 28, 29. In addition, detailed review of medical charts was conducted to better characterize the AMI phenotypes.…”
Section: Methodsmentioning
confidence: 99%
“…Validated standardized instruments were used to assess psychosocial and health status. These included (1) depression using the 9‐item Patient Health Questionnaire (PHQ‐9), with higher scores indicating increasing severity (range 0–27)19, 20, 21, 22; (2) perceived stress using the 14‐item Perceived Stress Scale (PSS), with higher scores indicating higher stress levels (range 0–40)23, 24; and (3) health status outcomes (patients’ physical limitations, angina frequency, and quality of life related to angina) using the Seattle Angina Questionnaire (SAQ; scores ranging from 0 to 100), with higher scores indicating better health status 25, 26, 27, 28, 29. In addition, detailed review of medical charts was conducted to better characterize the AMI phenotypes.…”
Section: Methodsmentioning
confidence: 99%
“…Arnold et al 25 evaluated the relationship between angina frequency from the SAQ and resource utilization and found that compared with patients who were angina free (score of 100 in angina frequency), patients with scores 0 to 30 in angina frequency had at least double the cost in resource utilization. The findings in of the present study exhibited similar results; for example, for both the PCI plus OMT and the OMTalone groups, costs were higher in patients with more severe angina.…”
Section: Discussionmentioning
confidence: 99%
“…To examine the economic impact of freedom from angina and related cost-effectiveness, we classified baseline angina frequency in an alternative way 24,25 : angina free (score, 100), monthly (score, 61 to 99), weekly (score, 31 to 60), and daily (score, 0 to 30). Onlineonly Data Supplement Table 7 and online-only Data Supplement Appendix A show the results of the cost and costeffectiveness analysis.…”
Section: Cost-effectiveness Analysis: Improvement Of Angina-related Hmentioning
confidence: 99%
“…For example, Keenan et al 22 assessed readmissions; Arnold et al, 23 Norris et al, 24 and Venkitachalam et al 25 Articles that investigate outcomes from the perspective of the health care system hold a place of similar importance. Although not directly experienced by patients, these outcomes affect society and represent meaningful end points to patients collectively.…”
mentioning
confidence: 99%
“…Past issues featured cost-effectiveness studies [31][32][33][34] and commentaries [35][36] and cost studies. 23,[37][38][39] To publish content of consequence-new knowledge that will advance the field and ultimately lead to better practice and policies-continues to be our goal. Articles that can satisfy our criteria come in many forms, with varied designs and focused on distinct outcomes.…”
mentioning
confidence: 99%